Peran Bimbingan Konseling dalam Membantu Siswa Kelas X Menentukan Karir di SMA Negeri 9 Denpasar - Benedita Ayu indah; Afrida Kanata; Mirna Meriati Londong; Putu Agus Semara Putra Giri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Career selection is a crucial aspect of student development, especially at the senior high school level. At this stage, students are faced with various choices that will shape their future. Therefore, career guidance through Counseling and Guidance (BK) services plays a strategic role in helping students understand their potential, gain career-related information, and make appropriate decisions regarding their career paths. This study aims to describe the role of  BK in assisting Grade X student at SMA Negeri 9 Denpasar in determining career that match their interest, talents, and personalities. A qualitative descriptive method was used, with data collected through observation, interview, and documentation. The result show tha BK services contribute positively to increasing students’awarenesss of the importance early career planning. Through activies such as individual counseling, classroom guindance, an the aptitude assessment tools, BK teacher are able to guide students in undestading themselves and choosing an educational or career path that suits them. Thus, BK plays a vital role in facilitating student’s career exploration and decision-making processes